INTESTINAL TRIGLYCERIDE ABSORPTION IN THE RAT : An Electron Microscopical Study - Cardell, Robert R. (The Rockefeller University Press, 1967)
This report provides information on the morphology of fat absorption in rat intestinal epithelial cells. Three types of experiments were performed: (a) intubation of corn oil into fasted rats, (b) injection of physiological fatty-chyme prepared from fat-fed donor rats into ligated segments of jejunum of fasted animals, and (c) administration of electron-opaque particles in corn oil and markers given concurrently with the fat. These results support the hypothesis that fat is absorbed by selective diffusion of monoglycerides and fatty acids from micelles rather than by pinocytosis of unhydrolized triglycerides. Evidence is presented that the pits between the microvilli, previously believed to function in the transport of fat, are not involved in this process. Instead they appear to contribute their contents to lysosomes in the apical cytoplasm. Arguments are offered that the monoglycerides and fatty acids diffuse from the micelle while the latter is associated with the microvillous membrane of the absorptive cell. These micellar components penetrate the plasma membrane and diffuse into the cytoplasmic matrix where they encounter the SER. Triglyceride synthesis occurs in the SER and results in the deposition of fat droplets within its lumina. The synthesis of triglycerides and their sequestration into the SER establishes an inward diffusion gradient of monoglycerides and fatty acids.